Ring statistics in disordered solids: a parallel algorithm for clusters with hundred thousands of atoms - Grigoriev, F.V.; Sulimov, V.B.; Tikhonravov, A.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2017)
The rings consisting of various number of atoms are basic structural elements in many disordered solids. In this paper, a parallel algorithm for calculating an approximate ring distribution function by the number of atoms is proposed. The algorithm is based on the Monte Carlo method and is applied to SiO_2 clusters consisting of up to 10^6 atoms. The efficiency of the algorithm is studied using up to 1024 computational cores.